Propaganda e coerção na política educacional do Estado Novo (1937-1945), em Pelotas/RS - Lemos, Vanessa dos Santos (2012)
This dissertation analyzes the elements of coercion and propaganda employed in education in the Estado Novo (1937-1945), especially in Pelotas - Rio Grande do Sul. The work examines how the policy of the dictatorship of Vargas manifested in education, which promoted the mechanisms massive participation of the school population in civic ceremonies, as well as adherence to the rules of society. The Vargas government, through its educational policy, sought to instill in Brazilian society, the cult leader, civic and patriotic values, forging a national identity. Are studied as the Civic Celebrations (Week Fatherland) and practices of physical education were employed in this process and how they were merged in the making of the New State pedagogical project, elements of the proposed Catholic teaching and the secular. It assessed the role of institutions in the school organization and monitoring of the community where they were inserted and how the state has co-opted families in the development of nationalization campaign. Perceived as a liberal discourse was linked to the practice in the joint dictatorship of accession and approval to the scheme. Demonstrates how the teaching of history was used in the formulation of an education grounded in a patriotic nationalism. Reflects on the promotion of physical education and a "civic" in caravans of Coloninhos in Camps and Scout groups, and how the military contributed to the discipline of Brazilian youth, so massive and coercive